A 'fownde patrone and second father' of the Marian Church: Antonio Buonvisi, religious exile and mid-Tudor Catholicism. Issue 2 (27th September 2018) - Smith, Frederick E.
Abstract: Despite receiving particular praise from a range of early modern commentators, from Nicholas Sander to Pedro de Ribadeneyra, most historians have seen the Italian merchant Antonio Buonvisi playing a fairly negligible role in the history of mid-Tudor Catholicism. This article challenges this interpretation. After reassessing some rather simplistic assessments of Buonvisi's religious beliefs, this article explores his actions and activities following his self-imposed exile from England in 1549. Using research conducted in both the State Archives of Lucca and the Vatican City, it suggests that Buonvisi played a far more significant role in ensuring the survival of English Catholicism over the first decades of the Reformation than is usually acknowledged. Indeed, it argues that Buonvisi may have helped lay core foundations for the Catholic restoration of Mary I's reign, the success of which has recently been highlighted by historians such as Eamon Duffy.